Clinical Relevance of Cervical Kinematic Quality Parameters in Planar Movement - Guo, Ze; Cui, Wei; Sang, Da‐cheng; Sang, Hong‐peng; Liu, Bao‐ge (Orthopaedic surgery, 2019)
Comprehending cervical spinal motion underlies the understanding of the mechanisms of cervical disorders. We aimed to better define the clinical relevance of cervical spine kinematics, focusing on quality parameters describing cervical spine planar motion. The most common study focuses were kinematic quality parameters after cervical arthroplasty and in normal subjects, patients with cervical degeneration, and patients with cervical deformities. Kinematic quality parameters are important for cervical degeneration prevention, being detected sooner than differences on imaging examinations and being significantly related to the degree of cervical degeneration. Kinematic quality parameters are effective for evaluating the changes of cervical motion pattern after cervical fusion and non‐fusion, assessing operative and adjacent segments in the early stages, and predicting adjacent segment degeneration. However, owing to current research limitations, and controversy about the changes of kinematic quality parameters after different surgical procedures, current assessments are limited to cervical spine flexion and extension. Different osteotomy methods of cervical deformity have different effects on cervical motion patterns and quality parameters. Choosing the most effective surgical method remains a challenge and kinematic quality parameters in cervical deformity are important future research topics. This review highlights the instantaneous center of rotation, the center of rotation, and the instantaneous axis of rotation as being important kinematic quality parameters of cervical spinal motion. These can be used to detect abnormal cervical mobility, to diagnose cervical degeneration, to design disc protheses, and to evaluate surgical effects earlier than other methods. Owing to limitations of research methods there is variation in the way parameters are defined by various researchers. No uniform standard exists for defining degenerative motion quality parameters in normal asymptomatic, degenerative, and postoperative patients. Therefore, further study is required. New study techniques and defining kinematic quality parameters in normal subjects will clarify the definitions of these parameters, enhancing their future clinical usefulness.